Produção de mudas de pêra por dupla-enxertia em interenxertos de marmeleiro utilizando o porta-enxerto japonês - Seifert, Karine Ester (2010)
Pear tree when grafted in quince rootstock they present reduced load. The Japonês quince tree could be an option a rootstock, however researches still revealed incompatibility in the nursery. Looking for to improve the seedlings production of pear using intergrafting, the objective of the present work went to develop a technology for producing seedlings of pear using 'Japonês' quince as a rootstock for pear through the use rustic graft quince, adopting the double-grafting process. Buds and cleft of the pear trees Seleta and Triunfo was grafted by the budding and cleft grafting, in cleft of 15 cm of the Portugal , Provence , Mendoza Inta-37 and Smyrna quince tree. The grafted were stored in cold camera (4ºC) for 24 hours. The cleft were grafted in Japonês roostock by cleft grafting. The treatments arranged in a 2 x 2 x 4 factorial scheme, the first factor composed of two pear cultivars ( Seleta and Triunfo ), the second factor by grafting the scion (grafting and budding) and the third factor by interstock of quince ( Portugal , Provence , Mendoza Inta-37 and Smyrna ), totaling 16 treatments with four replicates and five grafts per experimental unit, a total of 320 rootstocks and adopted DIC. After 60 days, the percentage of sprouting of the grafts and the filters were evaluated, repeated to the 120 days, besides the diameter and medium length of the grafts and the dry mass. The double-grafting is viable in the seedlings production pear tree intergrafting in the Japonês rootstocks, using with intergrafting Cydonia quince tree, also concluded that reduced the time the seedlings of pear and did not show visual incompatibility in the nursery, and the grafting was the best method of grafting, in which the cultivar Seleta showed higher growth of the grafts and interstock Smyrna and resulted in higher budding graft pear and Mendoza Inta-37 higher diameter